Improving nitrogen recommendations in Pacific Northwest sugarbeet production. Issue 2 (24th May 2016) - Tarkalson, David D.; Bjorneberg, Dave L.; Camp, Stacey; Dean, Greg; Elison, Dave; Foote, Paul
Abstract : The objectives of this study were to evaluate the N response of sugarbeet grown across the Pacific Northwest growing area and determine if N recommendation adjustments are needed by comparing the results to past recommendations. Earn 0.5 CEUs in Nutrient Management by reading this article and completing the quiz at www.certifiedcropadviser.org/certifications/self‐study/760 .